Enabling adenosine signaling to promote aged fracture healing - Hunter Newman; Yu-Ru V. Shih; Jiaul Hoque; Yuze Zeng; Naveen R. Natesh; Gavin Gonzales; Wendi Guo; Vijitha Puviindran; Colleen Wu; Benjamin A. Alman; Shyni Varghese (npj Regenerative Medicine)
Abstract Bone fractures and related complications are a significant concern for older adults, particularly with the growing aging population. Therapeutic interventions that promote bone tissue regeneration are attractive for geriatric fracture repair. Extracellular adenosine plays a key role in bone homeostasis and regeneration. Herein, we examined the changes in extracellular adenosine with aging and the potential of local delivery of adenosine to promote fracture healing using aged mice. Extracellular adenosine level was found to be significantly lower in aged bone tissue compared to young mice. Concomitantly, the ecto-5′-nucleotidase CD73 expression was also lower in aged bone. Local delivery of adenosine using injectable, in situ curing microgel delivery units yielded a pro-regenerative environment and promoted fracture healing in aged mice. This study offers new insights into age-related physiological changes in adenosine levels and demonstrates the therapeutic potential of adenosine supplementation to circumvent the compromised healing of geriatric fractures.